2021
DOI: 10.1038/s41598-021-95197-y
|View full text |Cite
|
Sign up to set email alerts
|

Induction of interferon response by high viral loads at early stage infection may protect against severe outcomes in COVID-19 patients

Abstract: Key elements for viral pathogenesis include viral strains, viral load, co-infection, and host responses. Several studies analyzing these factors in the function of disease severity of have been published; however, no studies have shown how all of these factors interplay within a defined cohort. To address this important question, we sought to understand how these four key components interplay in a cohort of COVID-19 patients. We determined the viral loads and gene expression using high throughput sequencing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…If performed too late after the contamination, the results of the test would probably be modified by the ongoing anti-infectious response in various proportions: IFN-γ secretion increased at the peak of the antiviral response, decreased at the time of immune reconstitution and even more so in case of cell exhaustion, or even increased persistently in case of long COVID. As suggested by other teams, but without a functional approach ( 30 , 38 ), a functional immunoassay performed early during the infection, or even before contamination, could predict the antiviral response against SARS-CoV-2, but also the response against other viruses or intracellular pathogens ( 52 ). This hypothesis is partly confirmed by our work but requires further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If performed too late after the contamination, the results of the test would probably be modified by the ongoing anti-infectious response in various proportions: IFN-γ secretion increased at the peak of the antiviral response, decreased at the time of immune reconstitution and even more so in case of cell exhaustion, or even increased persistently in case of long COVID. As suggested by other teams, but without a functional approach ( 30 , 38 ), a functional immunoassay performed early during the infection, or even before contamination, could predict the antiviral response against SARS-CoV-2, but also the response against other viruses or intracellular pathogens ( 52 ). This hypothesis is partly confirmed by our work but requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Type I and II IFN (i.e., IFN-α/β and IFN-γ, respectively) are the first-line cytokines against viral infections. While many studies have focused on type I and III IFN alteration in severe forms of COVID-19 ( 24 34 ), less research has been conducted on type II IFN deficiency ( 35 38 ). However, if type I IFN is a component of innate immunity, type II IFN is involved in both innate and adaptative immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we suggest that two mechanistic pathways could have adverse consequences on permissiveness: first, we hypothesize that a strong upregulation of interferon responses, in particular type I interferons, may play a role in preventing new virus progeny infection if present within the supernatant applied to naïve cells in the FFU assay. A direct correlation between interferon responses and viral load has recently been found [50]. Second, we hypothesize that DF-1 cells may not be permissible due to reasons related to the receptors such as APN or other specific receptors.…”
Section: Discussionmentioning
confidence: 76%
“…Several previous studies have shown the links between viral load dynamics and disease severity. Viral load affects the host gene expression and downstream response pathways ( 66 , 100 ). Blanco et al have shown that only 0.1% viral reads were detected post SC2 infection in A549, whereas in Calu3 cell line, 15% of the reads were detected.…”
Section: Discussionmentioning
confidence: 99%